2022
DOI: 10.31235/osf.io/b2n9x
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Let's report our rivals: how Chinese fandoms game content moderation to restrain opposing voices

Abstract: While crowdsourcing approaches in content moderation systems increase the governance capacity of social media, they also offer a loophole for malicious users to massively report and restrict disliked content.To fill the knowledge gap about large-scale, bottom-up attempts at restraining online expressions, we focus on a type of public and institutionalized mass reporting: anti-smear (反黑) campaigns within Chinese online fandom communities, where fans coordinate together and collectively report content they perce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(4 citation statements)
references
References 11 publications
0
4
0
Order By: Relevance
“…We manually examined the nodes in a few biggest clusters. We found that many users are fans of singers who reported undesired content in a coordinated way as Zhao and Chen [26] described (but on a much smaller scale). Besides, we also noticed many vigilante users in big co-reporting clusters who frequently reported inappropriate posts.…”
Section: Coordinated and Frequent Reportingmentioning
confidence: 55%
See 3 more Smart Citations
“…We manually examined the nodes in a few biggest clusters. We found that many users are fans of singers who reported undesired content in a coordinated way as Zhao and Chen [26] described (but on a much smaller scale). Besides, we also noticed many vigilante users in big co-reporting clusters who frequently reported inappropriate posts.…”
Section: Coordinated and Frequent Reportingmentioning
confidence: 55%
“…Giving ordinary people the right to report undesired content on social media may lead to a concern that users may weaponize this power to retrain the free expressions of others or stir up conflicts [6,11], especially in the authoritarian context [14]. Meanwhile, the tendency to report others is contagious and would intensify the online polarized atmosphere, and large-scale coordinated reportings could burden the content moderation system [26]. It is important to understand how social media react to such challenges.…”
Section: Literature Reviewmentioning
confidence: 99%
See 2 more Smart Citations